2002
DOI: 10.1001/archneur.59.3.439
|View full text |Cite
|
Sign up to set email alerts
|

The Neurological Masquerade of Intravascular Lymphomatosis

Abstract: Intravascular lymphomatosis is an uncommon disease with a myriad of potential neurological manifestations. Diagnosis requires a high index of suspicion and a pathological examination. If diagnosed early, aggressive chemotherapy is potentially curative, although the overall prognosis remains dismal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
89
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(93 citation statements)
references
References 24 publications
3
89
1
Order By: Relevance
“…Immunohistochemically, they were positive for B-cell markers including CD 20 ( Fig. 1-C3 (3,4). The present case also showed that the symptoms closely resemble cerebral infarction, and she was medicated as having cerebral infarction.…”
Section: Intravascular Large B-cell Lymphoma (Ivl) Is a Rare Systemicsupporting
confidence: 59%
“…Immunohistochemically, they were positive for B-cell markers including CD 20 ( Fig. 1-C3 (3,4). The present case also showed that the symptoms closely resemble cerebral infarction, and she was medicated as having cerebral infarction.…”
Section: Intravascular Large B-cell Lymphoma (Ivl) Is a Rare Systemicsupporting
confidence: 59%
“…Other important findings are bizarre neurological symptoms [9]. Most cases are diagnosed at autopsy because of misleading clinical features mimicking dementia, vasculitis, stroke, infection, or other neoplasm; in fact, in our case, all of these were considered as differential diagnoses.…”
Section: Discussionmentioning
confidence: 74%
“…(12)(13)(14) Intravascular large B-cell lymphoma shows a high incidence of neurological symptoms, including sensory and motor deficits, palsy, altered consciousness, and seizures, associated with CNS involvement at diagnosis. (14)(15)(16)(17) Considering the clinically aggressive behavior accompanied by various CNS risk factors and high rate of CNS involvement at diagnosis, the risk of CNS relapse is considered extremely high. (3,4,10,15,18) Although previous reports have described some IVLBCL patients with CNS relapse and the resulting poor prognosis, (15,19,20) no large-scale study focusing on CNS involvement in IVLBCL patients has been reported.…”
mentioning
confidence: 99%